Correlation Analysis of Efforts to Overcome Online Fraud by the Tokopedia E-Commerce Platform on Platform Usage Decisions - muhammad cahyadi putra (Informasi, 2025)
This study aims to determine whether there is a relationship between efforts to combat online fraud by the Tokopedia E-Commerce platform and the decision to use the platform by Tokopedia Users. The type of research used is quantitative research with data collection methods used, namely questionnaires, documentation, and literature studies. The sample used is Quota Sampling. The results of the study show that (1) There is a positive and significant correlation, based on the determination coefficient value (R2) is R2 = 0,345. The variable decision to use the platform is associated with 34,5% in the variable efforts to combat online fraud. (2) The value of the B Coefficient for the total X of 0,636 indicates that this relationship is quite strong between efforts to combat online fraud and the decision to use the platform. Therefore, the alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected.